Identification of Human UMP/CMP Kinase 1 as Doxorubicin Binding Target Using Protein Microarray. (September 2017) - Chen, Shuxian; Wang, Xu; Ye, Xianghui; Ma, Donghui; Chen, Caiwei; Cai, Junlong; Fu, Yongfeng; Cheng, Xunjia; Chen, Yun; Gong, Xiaohai; Jin, Jian
Doxorubicin (DOX) is a leading anthracycline drug with exceptional efficacy; however, little is known about the molecular mechanisms of its side effects, which include heart muscle damage, noncancerous cell death, and drug resistance. A total of 17, 950 human proteins expressed in HEK293 cells were screened and yielded 14 hits. Competitive and binding experiments further verified the binding of DOX to UMP/CMP kinase 1 (CMPK1), and microscale thermophoresis showed that DOX binds to CMPK1 with a K d of 1216 nM. In addition, we observed that the binding of DOX to CMPK1 activated the phosphorylation of CMP, dCMP, and UMP. A significant activation was observed at the concentration of 30 µM DOX and reached plateau at the concentration of DOX 30 µM, 150 µM, and 100 µM, respectively. DOX would add up stimulation of CMPK1 by DTT and overcome inhibition of CMPK1 by NaF, EDTA. In summary, we showed that DOX might bind to the nonactive site of CMPK1 and regulate its activity with magnesium.